Cross-National Comparisons of Internalizing Problems in a Cohort of 8952 Adolescents from Five European Countries: The EU NET ADB Survey - Georgia Drosopoulou; Foteini Vlasopoulou; Eleni Panagouli; Androniki Stavridou; Alexia Papageorgiou; Theodora Psaltopoulou; Maria Tsolia; Chara Tzavara; Theodoros N. Sergentanis; Artemis K. Tsitsika (Children, 2022)
Various factors such as family relationships, socioeconomic indicators, socio-cultural aspects, mental health problems and demographic variables, have been associated with internalizing problems in adolescence. The purpose of this study was to examine the prevalence of internalizing problems in adolescents from five European countries in comparison with risk factors. Using data from the European Network for Adolescent Behavior (EU NET ADB) survey, a cross-sectional school-based study of adolescents (from 14 to 17.9 years) was conducted. Data were retrieved from self-report questionnaires derived from Greece, Spain, the Netherlands, Iceland and Romania. Multiple logistic regression analysis overall and by country was held through estimation of odds ratios (OR) and 95% confidence intervals (95% CI). A total of 8952 adolescents participated in the study. According to the results, Greece (7.6%) and Romania (2.4%) presented with the lowest rates of internalizing problems, while Iceland presented the highest (11.1%). Internalizing problems were associated with lower school grades (adjusted OR = 1.21, 95% CI: 1.08–1.36), while the higher education level of parents was associated with lower odds of internalizing problems (adjusted OR = 0.75, 95% CI: 0.62–0.92). In country-specific analyses, factors that affected the likelihood of internalizing problems were gender, age, maternal and paternal unemployment. Variations detected in adolescents’ internalizing problems were determined by the socio-cultural context of each country. Cultural differences should be addressed thoroughly in further research, in order to better understand and intervene in aspects of internalizing problems in adolescence.